2020
DOI: 10.3389/fonc.2020.01166
|View full text |Cite
|
Sign up to set email alerts
|

m6A Reader YTHDC2 Promotes Radiotherapy Resistance of Nasopharyngeal Carcinoma via Activating IGF1R/AKT/S6 Signaling Axis

Abstract: N6-methyladenosine (m 6 A) modification has been reported as a critical regulator of gene transcript expression. Although m 6 A modification plays important roles in tumor development, its role in therapeutic resistance remains unknown. In this study, we aimed to examine the expression level of m 6 A-modification related proteins and elucidate the effect of m 6 A-related proteins on radiation response in nasopharyngeal carcinoma (NPC). Among the genes that participated in m 6 A modification, YTHDC2, a m 6 A re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 59 publications
1
53
0
Order By: Relevance
“…In non-small cell lung cancer, down-regulation of the m6A reader YTHDC2 promotes tumor progression and predicts poor prognosis ( Sun et al, 2020 ). YTHDC2 activates the IGF1R/Akt/S6 signal axis to promote radiotherapy tolerance for nasopharyngeal carcinoma ( He et al, 2020 ). A previous study also showed a single nucleotide polymorphism (SNP) rs2416282 in the YTHDC2 gene promoter region is significantly associated with ESCC susceptibility ( Yang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In non-small cell lung cancer, down-regulation of the m6A reader YTHDC2 promotes tumor progression and predicts poor prognosis ( Sun et al, 2020 ). YTHDC2 activates the IGF1R/Akt/S6 signal axis to promote radiotherapy tolerance for nasopharyngeal carcinoma ( He et al, 2020 ). A previous study also showed a single nucleotide polymorphism (SNP) rs2416282 in the YTHDC2 gene promoter region is significantly associated with ESCC susceptibility ( Yang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Through its N-KIAA1429 domain, KIAA1429 acts as a bridge between the catalytic core component of METTL3/METTL14/WTAP and the RNA substrate, thus affecting the installation of m6A at specific sites ( He et al, 2019 ). YTHDC2 is a protein from the DExD/H box RNA helicase family that plays an important role in mRNA transcription and maintenance of mRNA stability ( He et al, 2020 ). ZC3H13 is a CCCH zinc finger protein ( Zhu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that ZC3H13 may be a key upstream factor of nuclear factor-κB (NF-κB) that is responsible for NF-κB activation ( Luo et al, 2009 ). Numerous studies have shown that the five candidate m6A regulators participate in the occurrence and development of tumors, including proliferation, invasion, radiotherapy resistance, and prognosis ( Zalfa et al, 2017 ; Zhu et al, 2019 ; Chen et al, 2020 ; He et al, 2020 ; Xu et al, 2020 ). However, there are no reports on the relationship between the five candidate m6A regulators and childhood asthma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to promoting cisplatin resistance, FTO also contributed to radiation resistance in CSCC through up-regulation of [ 45 ]. YTHDC2 contributed to radioresistance in nasopharyngeal carcinoma (NPC) cells by binding to IGF1R mRNA and promoting the translation of the IGF1R transcript, leading to downstream activation of the IGF1R-AKT/S6 signaling axis [ 46 ].…”
Section: Rna Modifications In Stress Responsesmentioning
confidence: 99%